(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
One of the reasons for the transition of recurrent forms of bronchitis into chronic, in particular bronchial asthma, is the incompleteness of treatment, the lack of full recovery of the recovery stage in children. In the era of Covid-19- one of the reasons current situation is fact of advantageous use of inconclusive medical therapy,little attention is paid to the development and implementation of medical rehabilitation using non-medicated methods, the efficiency and safety of which is obvious.Kinezioterapiya (KT) is an effective non-drug methods of rehabilitation of children with diseases respiratory organs.